Effects of continuous positive airway pressure administered by a helmet in cats under general anaesthesia - Di Bella, Caterina; Araos, Joaquin; Lacitignola, Luca; Grasso, Salvatore; De Marzo, Linda; Crovace, Alberto Maria; Staffieri, Francesco (Journal of feline medicine and surgery, 2021)
Objectives The aim of this study was to evaluate the respiratory effects of non-invasive continuous positive airway pressure (CPAP) administered by a helmet in healthy cats under anaesthesia. Methods Fifteen healthy male cats scheduled for castration were anaesthetised with medetomidine (20 µg/kg), ketamine (10 mg/kg) and buprenorphine (20 µg/kg) intramuscularly. When an adequate level of anaesthesia was achieved, a paediatric helmet was placed on all subjects. The helmet was connected to a Venturi valve supplied with medical air and cats received the following phases of treatments: 0 cmH2O (pre-CPAP), 5 cmH2O (CPAP) and 0 cmH2O (post-CPAP). Each treatment lasted 10 mins. At the end of each phase an arterial blood sample was drawn. The following data were also collected: mean arterial pressure, respiratory rate, heart rate and the anaesthesia level score (0 = awake, 10 = deep anaesthesia). The alveolar to arterial oxygen gradient (P[A-a]O2) and the venous admixture (Fshunt) were also estimated. Data were analysed with two-way ANOVA (P <0.05). Results The arterial partial pressure of oxygen was higher (P <0.001) at CPAP (103.2 ± 5.1 mmHg) vs pre-CPAP (77.5 ± 7.4 mmHg) and post-CPAP (84.6 ± 8.1 mmHg). The P(A-a)O2 and the Fshunt were lower (P <0.001) at CPAP (4.4 ± 2.3 mmHg; 7.4 ± 3.1%) vs pre-CPAP (18.9 ± 6.4 mmHg; 22.8 ± 4.6%) and post-CPAP (15.6 ± 7.3 mmHg; 20.9 ± 4.6 %). No other parameters differed between groups. Conclusions and relevance Non-invasive CPAP applied by a helmet improves oxygenation in cats under injectable general anaesthesia.